EFFECT OF DIFFERENT LEVELS OF NITROGEN AND POTASSIUM FERTILIZERS APPLICATION ON NUTRIENT BALANCE AND YIELD OF BROCCOLI (Brassica oleraceae) - & Saleh, Dizayee (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
A study was conducted during fall season of 2015-2016 at Qwshtapa farm village of Grdmala, Erbil to study the effect of different rates of Nitrogen and Potassium fertilizers application on nutrient balance and yield of Broccoli. Treatments included 5 levels of nitrogen (0, 60,120,180 and 240 kg N ha-1), and 5 levels of potassium (0,150,300,450 and 600 kg K ha-1) in factorial experiment in RCBD with three replicates. The Diagnosis and Recommendation Integrated system (DRIS) methodology was applied to study nutrient balance. Results indicated that yields were 23.916 and 11.233 Mg ha-1 for N3K1 and N0K0 ,respectively. Values of Absolute Total (AT)"Nutrient Balance" were 45.82 and 9.96 for N0K0 and N3K1, respectively. From DRIS and ABI values it can be concluded that N and P were the most limiting nutrients for Broccoli production in this area of Kurdistan-Iraq and soil test was good indicator for soil fertility.